Exploring the Hypothetical Impact of Genetic Engineering on Ethnicity: An Analysis of a Large-Scale Data Set Retrieved From a Museal Setting - Döbler, Niklas 19XX- (Bioethics, 2026)
Critics of human genetic engineering warn that if ever put into practice, this will diminish human diversity, especially regarding skin color. Nonetheless, given the solid and shameful causal link between skin color and discrimination, the provocative question is whether to manipulate this feature and create children whose stereotype-aligning features reduce the risk of evoking hostility in the social environment. To address this possibility, we analyzed data from an interactive exhibit in a German museum that partly addresses these questions. Visitors could manipulate randomized features of a virtual child—for example, appearance and intelligence—to align them with their notion of a “perfect child.” Analysis of N = 13,641 virtual children showed an apparent effect on aligning skin color with a Caucasian type. This was true for extreme light and dark, randomly assigned initial skin colors, but stronger for the latter. This preference could reflect the attempt to align the hypothetical child's skin color with the creating visitors. We also analyzed the chosen skin-color-dependent distribution of designed intelligence based on previous findings showing that high intelligence is less desirable for Black than White persons. We revealed that virtual children with a chosen darker skin color were designed with relatively lower intelligence and a larger proportion of maximized and minimized values. Although most effects were small, they might indicate racial prejudices and/or the attempt to design virtual children with high alignment with normative stereotypes. Our findings provide an important starting point to empirically inform the critical and timely debate about human genetic engineering.